Principles of Guidance Counseling Organization - Anindya Indrie Ambarsari; Neng Tias Novitasari; Ayu Hanung Sekar Mawarni; Gusman Lesmana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to find out the importance of the principles of guidance and counseling to be a guide in providing counseling services, what are the principles of guidance and counseling in implementing counseling services. Guidance and Counseling Principles are guidelines or tools in carrying out the guidance and counseling service program process so that it runs according to regulations and has a positive impact on individuals. This principle will have a positive and flexible impact on its services, where the program provided will be in accordance with individual problems. The Guidance Counseling service also requires the role of the surrounding environment so that the program is carried out successfully and achieves the expected solution.